PEDAGOGICAL PRINCIPLES OF DEVELOPING SPIRITUAL COMPETENCE OF HIGH CLASS STUDENTS (Scientific journal of the Fergana State University, 2024)
This article describes the essence of the pedagogical foundations of developing the spiritual competence of high school students today. In order to improve the quality and efficiency of education, to develop a desire for professional growth among young people, in the wider understanding of the importance of personal competence, the aim is to turn to the cluster of professional competences of experts, many programs on the formation of their practical skills in subjects. A competent approach to education envisages teaching students to effectively use the competences formed in different situations in personal, professional and social life. Special attention is paid to the ability to use relevant knowledge, skills, and abilities when facing unexpected, uncertain, new, problematic situations.